Complete Genome Sequence Analysis of a Natural Reassortant Infectious Bursal Disease Virus in China - Chen, Feng (American Society for Microbiology, 2012)
A novel isolate of infectious bursal disease virus (IBDV) was designated GX-NN-L. The GX-NN-L IBDV was a very virulent infectious bursal disease virus (vvIBDV) isolated from broiler flocks in Guangxi province, China, in 2011. The GX-NN-L IBDV caused high mortality, immunosuppression, low weight gain, and bursal atrophy in commercial broilers. Here, we report the complete genome sequence of the GX-NN-L IBDV, a reassortment strain with segments A and B derived from very virulent strains and attenuated IBDV, respectively. These findings from this study provide additional insights into the genetic exchange between attenuated and very virulent strains of IBDV and continuous monitoring of the spread of the virus in chicken.